Changing agrometeorological conditions for maize (Zea mays L.) under the subtropical climate of northern Vietnam - Tran, Anh Thi Mai; Eitzinger, Josef (Asian Journal of Agriculture and Rural Development, 2025)
Maize is affected by changing growing and crop management conditions under ongoing climate change, posing potential production risks in the future. This study analyzes maize growing conditions in Northern Vietnam by utilizing the AGRICLIM agrometeorological indicator model. The climate projections are sourced from a global circulation model, supplemented by a regional climate model for two emission pathways (RCP4.5 and RCP8.5) spanning from 1951 to 2100. The three main local maize growing seasons (winter, spring, and forage maize season) were meticulously analyzed across four distinct time slices, encompassing annual, seasonal, and monthly scales. The results reveal that future agrometeorological conditions will generally become more extreme compared to current conditions. However, the calculated increase in heat stress days, heavy precipitation events, and drought stress days for maize shows varying changes across the specific maize growing seasons. For instance, drought and heat stress conditions may occur more frequently during the spring and forage maize seasons, while the risk of soil erosion and nitrogen leaching may rise in the winter and forage maize seasons. These findings will support the development of adaptation strategies under more adverse weather conditions for maize growing systems in Northern Vietnam.